STUDENTS’ HINDRANCES BEYOND ACADEMIC MATTERS IN APPLYING FOR INDONESIAN INTERNATIONAL STUDENT MOBILITY AWARDS (IISMA) A Study at Politeknik Aceh - Sabarniati, Sabarniati; Kurniawati, Kurniawati; Fitriani, Naria (Jurnal Visipena, 2024)
The Indonesian International Students Mobility Awards (IISMA) is a prestigious program launched by the Indonesian Ministry of Education and Culture (Kemdikbud). However, obstacles found that hampered the implementation of the program, especially at the Aceh Polytechnic. These obstacles both come from academic and non-academic factors. There, this study aims at administering factors that hinder the students of Politeknik Aceh from applying for IISMA program, and drawing possible solutions for the problems faced by the students. Moreover, this study also discussed about the relationship between Acehnese people’s way of thinking and their traditions, norms and cultures. The students were asked to fill in online questionnaires through Google Form Application. The result of the research showed that the majority of the students have lack motivation and understanding about the program. Only few students indicate great enthusiasm and insight about the output of living in another country. Moreover, More than half of the participants admitted their anxiety of studying overseas. Possible solutions to overcome the problems had been drafted. Counseling services, mentorship programs, peer support groups, and cultural preparation programs are amongst the ideal resolution that could be conducted to both minimize students’ anxiety and trigger their motivation to take part in IISMA program.